A Comparison of the Population Genetic Structure and Diversity between a Common (Chrysemys p. picta) and an Endangered (Clemmys guttata) Freshwater Turtle - Scott W. Buchanan; Jason J. Kolbe; Johanna E. Wegener; Jessica R. Atutubo; Nancy E. Karraker (Diversity, 2019)
The northeastern United States has experienced dramatic alteration to its landscape since the time of European settlement. This alteration has had major impacts on the distribution and abundance of wildlife populations, but the legacy of this landscape change remains largely unexplored for most species of freshwater turtles. We used microsatellite markers to characterize and compare the population genetic structure and diversity between an abundant generalist, the eastern painted turtle (Chrysemys p. picta), and the rare, more specialized, spotted turtle (Clemmys guttata) in Rhode Island, USA. We predicted that because spotted turtles have disproportionately experienced the detrimental effects of habitat loss and fragmentation associated with landscape change, that these effects would manifest in the form of higher inbreeding, less diversity, and greater population genetic structure compared to eastern painted turtles. As expected, eastern painted turtles exhibited little population genetic structure, showed no evidence of inbreeding, and little differentiation among sampling sites. For spotted turtles, however, results were consistent with certain predictions and inconsistent with others. We found evidence of modest inbreeding, as well as tentative evidence of recent population declines. However, genetic diversity and differentiation among sites were comparable between species. As our results do not suggest any major signals of genetic degradation in spotted turtles, the southern region of Rhode Island may serve as a regional conservation reserve network, where the maintenance of population viability and connectivity should be prioritized.